Titik Temu Nilai-Nilai Islam Nusantara Melalui Budaya Di Era Discruption - Wahyudi, M. Furqon; Hanif Fahruddin, Ahmad (Akademika, 2023)
The rapid flow of globalization accompanied by the rapid flow of digitalization provides its own pressure on Indonesian scientists in maintaining the Islamic values of the archipelago in the current era of rapid globalization of digitalization. This rapid flow is marked by the easy way of access to information or knowledge that will be used as a reference for scholars. Research using library research methods. The nature of this research is descriptive-qualitative, which is based on the quality of data that has been described and analyzed systematically and aims to describe and analyze certain phenomena or events that occur around. The sources of this research data are books, journals, and scientific writings related to the Islamic Values of the Archipelago and the Meeting Point of the Archipelago in the Era of Discruption. The results of the first research are that people can convey knowledge with young people to fellow people by utilizing digital and that the Islamic values of the archipelago can bring peace in living life, wherever they are. Both people believe that living in an environment with mutual respect will make them comfortable. Third, the community has a great opportunity through digitalization assistance to convey or socialize, that we can find Islamic values of the archipelago through the culture we believe in.